Integration of Mantics in Digital Qur'an Learning: An Experimental Study on Generation Z Muslims - Didin Hidayat; Shofa Marwah Muttaqin; Hikmal Mustofa; Moch Yaasin Abdul Halim; Diki Hilman Fauzi (Al-Alim: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the integration of logic in digital-based Qur'an learning, with a focus on the effectiveness of this approach towards the understanding of Muslim Generation Z. Using the library research method, this article summarizes and analyzes relevant literature from various sources, including classical books, scientific journal articles, and recent studies on digital learning and the characteristics of Gen Z. The results of the study indicate that a logical approach to Qur'an learning, if packaged in an interactive and contextual digital format, can improve textual and contextual understanding of the Qur'an in the younger generation. This integration also facilitates critical thinking and in-depth understanding of the meaning of the verses.